2014
DOI: 10.1371/journal.pone.0085712
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Oxidative Stress during Leprosy Multidrug Therapy: Impact of Dapsone Oxidation

Abstract: This study aims to assess the oxidative stress in leprosy patients under multidrug therapy (MDT; dapsone, clofazimine and rifampicin), evaluating the nitric oxide (NO) concentration, catalase (CAT) and superoxide dismutase (SOD) activities, glutathione (GSH) levels, total antioxidant capacity, lipid peroxidation, and methemoglobin formation. For this, we analyzed 23 leprosy patients and 20 healthy individuals from the Amazon region, Brazil, aged between 20 and 45 years. Blood sampling enabled the evaluation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 48 publications
2
22
0
2
Order By: Relevance
“…The reason behind it is that Microbial killing of lepra bacilli results in produc on of free radicals like nitric oxide. 21 These fi ndings are similar to the study done by Schalcher TR et al who also reported increased produc on of nitric oxide levels in leprosy pa ents as compared to healthy controls and no change in nitric oxide levels were seen a er treatment with an leprosy drugs 11,14 It seems that the disease process itself appears to be responsible for the detected nitric oxide increase in the body irrespec ve of the an leprosytreatment. 14 Studies have tried to quan fy oxida ve stress as per evalua ng levels of various enzymes and carbonyl proteins.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The reason behind it is that Microbial killing of lepra bacilli results in produc on of free radicals like nitric oxide. 21 These fi ndings are similar to the study done by Schalcher TR et al who also reported increased produc on of nitric oxide levels in leprosy pa ents as compared to healthy controls and no change in nitric oxide levels were seen a er treatment with an leprosy drugs 11,14 It seems that the disease process itself appears to be responsible for the detected nitric oxide increase in the body irrespec ve of the an leprosytreatment. 14 Studies have tried to quan fy oxida ve stress as per evalua ng levels of various enzymes and carbonyl proteins.…”
Section: Discussionsupporting
confidence: 85%
“…The present study is a prospec ve study which includes 60 cases of healthy controls and 30 cases of leprosy pa ents. In modern era, interest has grown in inves ga ng the role played by reac ve oxygen species or oxida ve stress in leprosy leprosy by inves ga ng one or more of the oxidant markers like Malondialdehyde (MDA) and an oxidant markers, including SOD, catalase, vitamin E, vitamin C. [11][12][13][14] Lipid peroxida on is involved in pathogenesis of many disease processes when the imbalance occurs between produc on of reac ve oxygen species and protec ve an oxidant system. Malondialdehyde (MDA) is a marker of lipid peroxida on.…”
Section: Discussionmentioning
confidence: 99%
“…CFZ has been reported to influence antioxidant capacity 44 and the production of reactive oxygen species. 45 To assay for the concentrations of some of these redox analytes (cysteine, cystine, glutathione and glutathione disulfide), samples were derivatized with 2,3-dinitrofluorobenzene followed by HPLC analysis as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…The current strategy for leprosy control recommended by the World Health Organization (WHO) is based on multidrug therapy (MDT) that consists of the combination of rifampicin, clofazimine and dapsone (4,4'-diaminodiphenylsulfone, DDS) for multi-bacillary leprosy patients and rifampicin and DDS for pauci-bacillary leprosy patients [ 3 ]. DDS therapy is responsible for hematological adverse reactions, such as methemoglobinemia and anemia [ 6 , 7 ]. These effects are associated with the hydroxylamine metabolite of DDS (DDS-NHOH) that is formed through N-hydroxylation by hepatic cytochromes P450, particularly CYP2C9 and CYP2C19 [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…DDS therapy is responsible for hematological adverse reactions, such as methemoglobinemia and anemia [ 6 , 7 ]. These effects are associated with the hydroxylamine metabolite of DDS (DDS-NHOH) that is formed through N-hydroxylation by hepatic cytochromes P450, particularly CYP2C9 and CYP2C19 [ 6 , 8 ]. The principal targets of hydroxylamine compounds in humans are erythrocytes, involving mainly the production of high rates of methemoglobinemia and a significant reduction in erythrocytic lifespan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%